2001
DOI: 10.1021/jp0037807
|View full text |Cite
|
Sign up to set email alerts
|

Remote Photocatalytic Activity as Probed by Measuring the Degradation of Self-Assembled Monolayers Anchored near Microdomains of Titanium Dioxide

Abstract: A cross-linked self-assembled monolayer (SAM) of octadecyltrichlorosilane (OTS) was chemisorbed on well-defined structures, comprised of alternating microstripes of TiO2 and silicon. The kinetics of the photodegradation of the anchored SAM on the hybrid structure was then measured in situ by FTIR under controlled humidity and surface temperature. It was found that mineralization of the aliphatic chains anchored to the inert silicon domains can occur, even when these chains are located as far as 20 μm away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 29 publications
7
82
0
1
Order By: Relevance
“…• Built Environment Self-cleaning coatings [34,38,39,[41][42][43][44][45][46][47][48][49][50]. Non-spotting glass [47,51].…”
Section: Titania Applicationsmentioning
confidence: 99%
“…• Built Environment Self-cleaning coatings [34,38,39,[41][42][43][44][45][46][47][48][49][50]. Non-spotting glass [47,51].…”
Section: Titania Applicationsmentioning
confidence: 99%
“…[14] While several studies suggested that O 2 À , a species that participates in the photodegradation of organics, [15] has very low mobility and is deactivated by releasing an electron to TiO 2 without reacting with other chemical species, [16] other studies have claimed that the oxidizing species may diffuse quite a long way on the photocatalyst surface. [11,17,18] Herein we show for the first time that molecules located on dark areas in the vicinity of illuminated domains of titanium dioxide might be prone to an attack by oxidizing species that diffuse out from the illuminated areas. Moreover, we will show that the dark domains may enhance the overall efficiency of the degradation process.…”
Section: Introductionmentioning
confidence: 91%
“…The active oxygen species can diffuse in the air phase, although diffusion rate is slow, and oxide the organic substance far from the locus of their formation. 50,51 As to the TiO 2 -SiO 2 composite lms, the HDTMS molecules on TiO 2 particles can be decomposed directly, but the HDTMS molecules on SiO 2 particles were decomposed through diffusion of photogenerated active oxygen species at a slower rate. Therefore, it is reasonable that the SiO 2 -TiO 2 composite lm and the triple-layer lm, which possess a low coverage rate of TiO 2 particles on the surface, showed a slower rate of photocatalytic oxidation.…”
Section: 47mentioning
confidence: 99%